Effect of Impact Load on Dynamic Buckling of Steel Lattice Arch - Liu, M.S.; Li, J.Y.; Tian, Z.X.; Zhu, C.W.; Ju, J.S. (Проблемы прочности, 2017)
In this study, test results and numerical simulation data are jointly analyzed to investigate the dynamic buckling of the steel arch under impact load. A series of impact tests of the triangular lattice steel arch are conducted to study the effect of the impact velocity and rise-to-span ratio on the structure buckling. The experimental results are compared with the numerical simulation ones, including arch buckling and strain data, which show the efficiency of the numerical simulation in performing the arch dynamic response calculation. It is also revealed that the impact velocity has a drastic effect on the steel arch buckling, and the arch impact resistance can be improved by increasing the rise-to-span ratio.